The Effect of Higher Education on Women's Obesity and Smoking: Evidence from College Openings in Turkey - Badi H. Baltagi; Alfonso Flores-Lagunes; Haci M. Karatas (Institute of Labor Economics (IZA), 2022)
This paper analyzes the relationship between higher education and body weight and smoking behavior among women in Turkey. We exploit the largely exogenous and substantial increase in the openings of universities throughout Turkey. Based on the spatial and temporal variability of university openings, we construct college accessibility measures at the level of the city of residence when the woman turned 17 years of age to serve as instruments for college enrollment. The college accessibility measures have a substantial 5 percentage-point (about 80%) impact on the probability of college enrollment, and we show they also impact lower levels of schooling, likely through expectations. Using the college accessibility measures as instruments for college enrollment, we find that a one percentage point increase in the probability of college enrollment reduces BMI by about 0.21% and the probability of being classified as obese by 0.44 percentage points. Regarding smoking, we find that a similar increase in the probability of college enrollment increases the probability of being a current smoker by 0.73 to 1.1 percentage points. Both results contrast with previous findings for Turkey and other countries, likely denoting heterogeneities in the level of schooling considered (primary or secondary versus tertiary) and in the level of economic development of these countries.
Keywords: I12; I21; I23; I26; C26; 330; health; tertiary education; women; body mass index; obesity; smoking; Turkey